Business Process Innovations for Courier Service Sector: Case Study in J&T Dungun - Harahap, Afif Zuhri Muhammad Khodri; Atiqah, Nur Fatwa; Abd Sukor, Hanis Athirah; Mohd Rahim, Muhammad Kamal Fudhail; Mohd Apandi, Fatin Syafiqah; Saedon, Aiezwa Zetty Syafina (UUM Press, 2023)
This research explores the journey of a logistics and delivery service provider, tracing its development from a local entity to a significant industry participant. Through a customer-focused approach, the company employs advanced tools and a solid foundation to provide reliable logistical services. It has gained acclaim for its effective transportation-related solutions, establishing a benchmark for quality. Furthermore, this study focusses on the J&T Express company's innovative solutions, technological advancements, and dedication to customer satisfaction have propelled it to a leadership position in the logistics sector. This study highlights the importance of process optimization and technology integration, evident through the case of J&T Express. The adoption of automated wrapping, labelling, and barcode scanning processes has significantly streamlined operations, reduced reliance on manual labor, and improved efficiency. This transformation has led to cost savings, increased operational performance, and scalability. However, the study also underscores the significance of maintaining a balance between automation and human interaction to ensure a successful integration of technology in business operations.